From Maternal Trauma to Social Mission: Transforming Personal Loss into Social Support (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The loss of a child is one of the most traumatic events, capable of significantly impacting a mother's psycho-emotional state, social roles, and life prospects. Even while caring for a seriously ill child, the lives of parents, and especially mothers, change dramatically, accompanied by high levels of stress, emotional exhaustion, social isolation, and significant financial strain on the family. However, despite the high level of psycho-emotional trauma, some people are able to transform their own difficult experiences into a source of personal development, recovery, or the formation of prosocial activities and even leadership. This is especially evident in the processes of establishing charitable foundations and organizations.The purpose of this article is to analyze the relationship between the traumatic experience of loss and the process of subsequent personal growth in the mother, as well as the formation of a social mission through charitable work. Particular attention is paid to:The mechanisms of finding meaning and purpose after the loss of a child;The role of altruistic activity in the process of psychological rehabilitation;The study explores the potential and specific features of charitable organizations in providing support to families and mothers in crisis situations.The methodological basis of this work is an analysis of contemporary psychological, sociological, and medical-social research on maternal grief, post-traumatic rehabilitation, and personal growth. A practical example of the implementation of these theoretical principles is the case of Tatyana Artemyeva and her creation of the charitable foundation "NeuroChildren" for children with brain diseases. Ms. Artemyeva was able to transform her own experience of loss into systemic assistance for children, mothers, and families facing difficult life circumstances.These results confirm the role of charitable activity not only as a mechanism for providing social support to others but also as a key factor in reconstructing one's own identity, creating a new meaning in life, and developing social leadership after trauma.